Mapping study of food-grain value chains in Eastern Africa - Technical Centre for Agricultural and Rural Cooperation; Kilimo Trust (CTA / Kilimo Trust, 2017)
Agriculture is one of the East African Community’s most important economic sectors. The major staple foods in the region are maize, rice, potatoes, bananas, cassava, wheat, sorghum, millet and pulses. However, agricultural production in the region is prone to the vagaries of climate change, fluctuating food prices, a rapidly growing population in the urban areas and natural resource degradation. Even though governments have intensified efforts to develop agriculture in the region, intra-regional trade in staple food grains is still very low. The main objective of the study is to provide CTA with an understanding of the salient features of the four food-grain value chains in the EAC region, and information and possible entry points about the types of commodities to be supported and the nodes of the food-grain value chains that interventions should focus on.